TRANSFORMASI PENDIDIKAN HUMANISTIK BERBASIS AKULTURASI BUDAYA DALAM MEMBANGUN KECERDASAN SOSIAL PESERTA DIDIK DI ERA DIGITAL - Pepen Supendi; Hafiz, Fadlan; Edgardo Kaka Cahyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the transformation of humanistic education based on cultural acculturation as a strategy for developing students' social intelligence in the digital era. This study applies a qualitative approach utilizing literature study methods. Literature study is used to examine the concept of humanistic education, the process of cultural acculturation, the characteristics of the digital era, and the concept of social intelligence from various theoretical and empirical studies. The results of the study indicate that the integration of local wisdom values (e.g., mutual cooperation, deliberation, tolerance) into humanistic education practices can strengthen students' empathy, interpersonal communication, and collaboration—core components of social intelligence—although digital challenges such as individualism and decreased face-to-face interaction still need to be anticipated. The proposed implementation model includes culture-based collaborative learning, humanistic reflective practice, strengthening school culture based on local wisdom, and the humanistic use of technology as a medium for cultural expression. This study recommends curricular integration and strengthening teacher capacity, as well as school-cultural community collaboration as initial steps in implementation. Thus, education based on humanism and local culture is an effective strategy for developing students with character.